Structurally Ordered Fe3Pt Nanoparticles on Robust Nitride Support as a High Performance Catalyst for the Oxygen Reduction Reaction - Liu, Quanbing; Du, Li; Fu, Gengtao; Cui, Zhiming; Li, Yutao; Dang, Dai; Gao, Xiang; Zheng, Qiang; Goodenough, John B. (Advanced energy materials, 2019)
The commercialization of fuel cell technologies requires a significant reduction in the amount of expensive platinum catalyst in the cathode while still maintaining high catalytic activity and stability. Herein a cost‐effective, highly durable, and efficient catalyst consisting of ordered Fe3Pt nanoparticles supported by mesoporous Ti0.5Cr0.5N (Fe3Pt/Ti0.5Cr0.5N) is demonstrated. The Fe3Pt/Ti0.5Cr0.5N catalyst exhibits a five‐fold increase in mass activity relative to a Pt/C catalyst at 0.9 V for the oxygen reduction reaction. More importantly, the catalyst shows a minimal loss of activity after 5000 potential cycles (9.7%). The enhanced activity of the ordered Fe3Pt/Ti0.5Cr0.5N catalyst, in combination with its enhanced stability, makes it very promising for the development of new cathode catalysts for fuel cells. An efficient and cost‐effective nitride‐supported, ordered Fe3Pt electro‐catalyst that exhibits significant enhancement in catalytic activity and durability for the oxygen reduction reaction (ORR) when compared to disordered Fe3Pt/C and Pt/C is demonstrated.